Security in Computing (Fifth edition) - Charles P. Pfleeger; Shari Lawrence Pfleeger; Jonathan Margulies (Prentice Hall, 2020)
1. Introduction. 2. Toolbox: Authentication, Access Control, and Cryptography. 3. Programs and Programming. 4. The Web—User Side. 5. Operating Systems. 6. Networks. 7. Databases. 8. Cloud Computing. 9. Privacy. 10. Management and Incidents. 11. Legal Issues and Ethics. 12. Details of Cryptography. 13. Emerging Topics...